KAJIAN NUMERIK MASALAH SYARAT BATAS MELALUI PENYELESAIAN MATRIKS TRIDIAGONAL (Studi Kasus : Menghitung Potensial Listrik) - Juwariyah, Tatik (Bina Teknika, 2017)
A numerical study of the solution of boundary value problems with the tridiagonal matrix approach has been done. The case studied is computing the electrical potential expressed by 1D Poisson’s equation with boundary conditions. The 1D Poisson’s equation are then discreted with the finite different method so as to form a system of linier equations. The system of non homogeneous linear equations that can be formed is a tridiagonal matrix. Then the matrix is solved by Gaussian elimination algorithm. On this study, the algorithm is implemented on three programming languages namely, Fortran, Java and MATLAB.